Analisis Adaptasi MAN 2 Deili Serdang terhadap Perubahan Kurikulum Pendidikan - Sitorus, Agatha Sescio Ellano; Butarbutar , Yosefine Lasmawaty; Andini, Zafia Ranti; Habibillah, M.Soleh (Indra Institute Research & Publication, 2025)
This study examines how MAN 2 Deli Serdang adapted to the change of the 2013 curriculum to the Independent Curriculum. This study uses numbers and stories to collect information. The numbers come from student surveys, and the stories come from conversations with the Vice Principal and teachers in interviews. The results of the study show that the school, especially the teachers, already have a good attitude and have tried various ways of adjustment such as teacher training, changes in teaching materials, and the use of project-based learning (P5). However, there are still some major problems. Parents are worried about the cost of the P5 project, and students prefer the old way of learning now that direct teaching has decreased. The study concluded that the school has done a fairly good job in adapting, but needs more help in terms of teacher support, talking with parents, and increasing school resources so that the new curriculum can run better.